СИНТАКСИЧЕСКАЯ ОРГАНИЗАЦИЯ ОПИСАНИЙ ИНТЕРЬЕРА В ХУДОЖЕСТВЕННОМ ДИСКУРСЕ - Бирюкова, Д.В. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 1970)
Статья посвящена анализу синтаксической организации описаний интерьеров, исследованию специфики использования простых и сложных предложений и их типов и выявлению доминирующих синтаксических моделей в англоязычном художественном дискурсе. Установлено, что для описания интерьера чаще используются сложные предложения, где доминирующую позицию занимает гипотаксис.Ключевые слова: гипотаксис, микротекст, описание интерьера, паратаксис, период, простое предложение. Бірюкова Д.В. Особливості синтаксичної організації описів інтер’єру в художньому дискурсі. Стаття присвячена аналізу синтаксичної організації описів інтер’єру, дослідженню специфіки використання простих і складних речень та їх типів і виявленню домінуючих синтаксичних моделей в англомовному художньому дискурсі. Встановлено, що для опису інтер’єру частіше використовуються складні речення, в яких домінуючу позицію займає гипотаксис.Ключові слова: гіпотаксис, мікротекст, опис інтер'єру, паратаксис, період, просте речення. Biryukova D.V.. Features of syntactic organization of interior descriptions in literary discourse. This article analyzes the syntactic organization of interiors descriptions, studies the specific use of simple and compound sentences and their types and identifies the dominant syntactic patterns in English literary discourse. It was found that compound sentences with hypotaxis prevailed in interior descriptions.Key words: description of the interior, hypotaxis, microtext, parataxis, period, simple sentence.